(untitled) (Iraqi Journal of Medical Sciences, 2004)
Objectives: Breast cancer is the most common site-specific cancer in women and is the leading cause of death from cancer in females at 40-50 years of age. This is a retrospective study of 100 cases of carcinoma of the breast diagnosed by histopathology were analyzed to detect the most common presenting complaint & the risk factors of Ca Breast in Iraqi female patients during the Embargo. Methods: The medical records of 100 patients with Ca breast that were diagnosed by histopathology were reviewed. The study was conducted in Al-Kadhimiya Teaching Hospital and involved patients who were admitted to this hospital during the period (January 1992-December 2001). Results: The age of our patients range from 25-75 years, with a maximum age group distribution (48%) at 35-44 years. 64 patients with Ca breast presented with painless breast lump, 14 patients presented with painful lump and 10 patients presented with nipple discharge (bloody discharge). 71 patients with Ca breast are premenopausal & 29 of these (40.8%) have history of regular menstrual cycle while 42 of these (59.2%) have history of irregular menstrual cycle. There are 45 multifarious patients that breast fed their children, while another 47 multiparous patients that did not breast feed their children. Thyroidectomy was found to be submitted to 23 patients with Ca breast due to goiter prior to developing Ca breast. There are 33 patients got history of preexisting benign breast condition, while14% of our patients have positive family history of Ca breast. The upper lateral quadrant of the breast is the common site of involvement with Ca breast (72%). Conclusion: Breast cancer is the most common tumor of females with a general tends towards an increase in younger age group. It is really important for any female who indeed care about her general health to start self examination for her breast as early as possible starting at 18 years of age on certain time intervals, particularly when she feels any symptoms (like the presence of breast lump, pain, nipple discharge…etc.) must hurry to seek medical consultation. Key words: Ca breast, presentation, embargo. Iraqi J Med Sci, 2004; Vol. 3 (1): 59-61